Evaluating Science Textbooks for Saudi Intermediate Stage in the light of Requirements of the Integration Approach among Science, Technology, Engineering and Mathematics (STEM) - Ali Alahmadi (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This research aims to evaluate the Saudi intermediate science textbooks in the light of requirements of the integration approach STEM. The researcher implemented the descriptive method via designing a list of requirements of the STEM approach. An analysis card as well as a questionnaire were also designed in the light of such a list. Tools were validated, then administered to the sample of the study as represented by the topics of the science textbooks, in addition to the sample derived from specialists in STEM. Statistical analyses of the available data pinpointed out that fulfilling the requirements of integrated knowledge as well as integrated skills within the content of the science curriculum was generally poor. Ratio amounted to (44.1%) and (42.7%), respectively. Requirements pertaining to scientific, technical and engineering practices along with requirements of futuristic jobs as well as professional awareness proved to be very poor. The ratio amounted to (11.9%) and (1.14%) respectively. Moreover, results illustrated that specialists in STEM had a consensus that requirements of integrated knowledge, integrated skills, as well as requirements pertaining to scientific, technical and engineering practices were moderately fulfilled. Such requirements were poor when they pertained to futuristic professions and professional awareness. The researcher suggested a proposed vision for fulfilling such requirements in the content of science textbooks.